Neonatal surgery. Pediatric Hospital. Cienfuegos 2000-2003. - Jayce Díaz Díaz; Anabel Ledesma; Yanet Rojas Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Fundament: In surgery the major percentage of deaths is related to the newborns who have to be operated, and among them, congenital malformations are one of the first causes of deaths all over the world. Objective: To describe neonatal surgery in the Paediatric Hospital from Cienfuegos province. Methods: Retrospective descriptive study to the 22 newborns aged less than 28 days who were surgically intervened from January 2000 to December 2003 at the ¨Paquito Gonzalez Cueto¨ Paediatric Hospital from Cienfuegos province. The variables under study were: age, sex, nutritional state, disorders, stay at the intensive care unit period of mechanical ventilation, postoperatory complications and follow up. Results: The Surgery was done to neonates older than 72 hours of being born, mainly males, with a weight more than 2500g. Intestinal atrasias were the most common congenital malformations and with longer hospital stay at the ICU . mechanical ventilation was prolonged during the postoperatory between 48 and 72 hours. The most frequent postoperatory complications were the syndrome of multiple organic dysfunction and evisceration . The final evolution was favourable in almost all the operated newborns.